Use of Signal-Mediated Amplification of RNA Technology (SMART) to Detect Marine Cyanophage DNA. (March 2002) - Hall, M.J.; Wharam, S.D.; Weston, A.; Cardy, D.L.N.; Wilson, W.H.
Here, we describe the application of an isothermal nucleic acid amplification assay, signal-mediated amplification of RNA technology (SMART), to detect DNA extracted from marine cyanophages known to infect unicellular cyanobacteria from the genus Synechococcus . The SMART assay is based on the target-dependent production of multiple copies of an RNA signal, which is measured by an enzyme-linked oligosorbent assay. SMART was able to detect both synthetic oligonucleotide targets and genomic cyanophage DNA using probes designed against the portal vertex gene (g20). Specific signals were obtained for each cyanophage strain (S-PM2 and S-BnM1). Nonspecific genomic DNA did not produce false signals or inhibit the detection of a specific target. In addition, we found that extensive purification of target DNA may not be required since signals were obtained from crude cyanophage lysates. This is the first report of the SMART assay being used to discriminate between two similar target sequences.